Effects of Salinity on the Biodegradation of Polycyclic Aromatic Hydrocarbons in Oilfield Soils Emphasizing Degradation Genes and Soil Enzymes - Li, Yang; Li, Wenjing; Ji, Lei; Song, Fanyong; Li, Tianyuan; Fu, Xiaowen; Li, Qi; Xing, Yingna; Zhang, Qiang; Wang, Jianing (Frontiers in Microbiology, 2022)
The biodegradation of organic pollutants is the main pathway for the natural dissipation and anthropogenic remediation of polycyclic aromatic hydrocarbons (PAHs) in the environment. However, in the saline soils, the PAH biodegradation could be influenced by soil salts through altering the structures of microbial communities and physiological metabolism of degradation bacteria. In the worldwide, soils from oilfields are commonly threated by both soil salinity and PAH contamination, while the influence mechanism of soil salinity on PAH biodegradation were still unclear, especially the shifts of degradation genes and soil enzyme activities. In order to explain the responses of soils and bacterial communities, analysis was conducted including soil properties, structures of bacterial community, PAH degradation genes and soil enzyme activities during a biodegradation process of PAHs in oilfield soils. The results showed that, though low soil salinity (1% NaCl, w/w) could slightly increase PAH degradation rate, the biodegradation in high salt condition (3% NaCl, w/w) were restrained significantly. The higher the soil salinity, the lower the bacterial community diversity, copy number of degradation gene and soil enzyme activity, which could be the reason for reductions of degradation rates in saline soils. Analysis of bacterial community structure showed that, the additions of NaCl increase the abundance of salt-tolerant and halophilic genera, especially in high salt treatments where the halophilic genera dominant, such as Acinetobacter and Halomonas. Picrust2 and redundancy analysis (RDA) both revealed suppression of PAH degradation genes by soil salts, which meant the decrease of degradation microbes and should be the primary cause of reduction of PAH removal. The soil enzyme activities could be indicators for microorganisms when they are facing adverse environmental conditions.